DEGREE OF PRESERVATION OF IGNEOUS ZONATION IN ZIRCON AS A SIGNPOST FOR CONCORDANCY IN U/PB GEOCHRONOLOGY - Connelly J.N. (My University, 2001)
Zircon crystallized from felsic magmas typically (if not ubiquitously) develop compositional growth zonation that is easily imaged by cathodoluminescence (CL). This zonation represents inherently unstable chemical gradients that are preserved only by virtue of slow diffusion. CL images from igneous rocks that have experienced single metamorphic events suggest that chemical diffusion occurs during metamorphism and causes progressive blurring and eventual eradication of sharp-edged, primary zonation in magmatic zircon. Characterizing the range of zonation preservation in a single zircon population using CL imaging can provide a qualitative estimate of the relative degree of diffusion that occurred within that population. The integration of CL imagery and conventional U/Pb data indicates that extra-crystalline Pb loss (and therefore discordance) has occurred where chemical diffusion has operated at scales sufficient to modify primary zonation. Whereas the degree of diffusion and attendant Pb loss cannot be quantitatively estimated, this integrated data defines a strong relationship between discordance and the relative degree of preservation of zonation in zircon. This link provides a useful tool for conventional U/Pb geochronology to better predict the degree of discordance in samples of meta-igneous rocks. It also confirms that penetrative, thermally driven Pb loss occurs in zircon that has accumulated metamictization.
Keywords: CATHODOLUMINESCENCE; METAMORPHISM; U/PB GEOCHRONOLOGY; ZIRCON; ZONATION